Efecto de la capacidad antioxidante y antiglicación in vitro del extracto acuoso de Stevia rebaudiana Bertoni. - Escutia-López, K. N.; Cruz-ortiz, R.; Cano-Sampedro, E.; García-rojas, V.; Rodríguez-Rivero, Y.; Sánchez-Pardo, M. E.; Mora-Escobedo, R. (Revista Bio Ciencias, 2020)
Diabetes is a metabolic disorder characterized by chronic hyperglycemia with alterations in the metabolism of carbohydrates, fat, and proteins. Supplementation with natural antioxidants could have a beneficial effect on diabetic’s health, therefore the objective of this study was to determine the effect of an aqueous extract of Stevia rebaudiana Bertoni (AES) at different concentrations on the capacity to inhibit the formation of fluorescent Advanced Glycation Endproducts (AGEs) in a 21 days glycation BSA/glucose/fructose model. It was evaluated the antioxidant capacity of these extracts (Total phenolic content, Ferric reducing power, Hydroxyl radical and DPPH free radical scavenging activity). Additionally it was performed UHPLC MS/MS steviosides quantification. AES exhibit a high anti-glycation activity. The total polyphenol content of extracts of S. rebaudiana was 20.1±0.4mg GAE/g. The percent inhibition on hydroxyl radical scavenging was 13.03, 14.36 and 17.51%, for each concentration in a dose-dependent manner. For DPPH radical scavenging, the lowest concentration (2.5 mg/mL) showed higher activity, with an inhibition of 60% to 72.37%. AES showed an antioxidant capacity which may be due to compounds with antioxidant activity reported in stevia leaves as phenolic compounds which also exhibit a high anti-glycation activity. Antioxidant compounds of AES can suppress the effect on AGEs formation and protein oxidation.